RAPTOR Controls Developmental Growth Transitions by Altering the Hormonal and Metabolic Balance - Salem, Mohamed A; Li, Yan; Bajdzienko, Krzysztof; Fisahn, Joachim; Watanabe, Mutsumi; Hoefgen, Rainer; Schöttler, Mark Aurel; Giavalisco, Patrick (Plant physiology (Bethesda), 2018)
Vegetative growth requires the systemic coordination of numerous cellular processes, which are controlled by regulatory proteins that monitor extracellular and intracellular cues and translate them into growth decisions. In eukaryotes, one of the central factors regulating growth is the serine/threonine protein kinase Target of Rapamycin (TOR), which forms complexes with regulatory proteins. To understand the function of one such regulatory protein, Regulatory-Associated Protein of TOR 1B (RAPTOR1B), in plants, we analyzed the effect of mutations on growth and physiology in Arabidopsis ( ) by detailed phenotyping, metabolomic, lipidomic, and proteomic analyses. Mutation of resulted in a strong reduction of TOR kinase activity, leading to massive changes in central carbon and nitrogen metabolism, accumulation of excess starch, and induction of autophagy. These shifts led to a significant reduction of plant growth that occurred nonlinearly during developmental stage transitions. This phenotype was accompanied by changes in cell morphology and tissue anatomy. In contrast to previous studies in rice ( ), we found that the Arabidopsis mutation did not affect chloroplast development or photosynthetic electron transport efficiency; however, it resulted in decreased CO assimilation rate and increased stomatal conductance. The mutants also had reduced abscisic acid levels. Surprisingly, abscisic acid feeding experiments resulted in partial complementation of the growth phenotypes, indicating the tight interaction between TOR function and hormone synthesis and signaling in plants.